Guidebook for the Scientific Traveler : Visiting Physics and Chemistry Sites Across America - Nickell, Duane S. (Book collections on Project MUSE., 2010)
A one-of-a-kind guidebook for planning physics-and-chemistry-themed trips across the U.S.--from the Lawrence Livermore National Laboratory in California to the Florida Solar Power Energy Center, from the Titan Missile Museum in Tucson to the Anheuser-Busch Brewery in St. Louis.